Cumulative versus end‐of‐course assessment: effects on self‐study time and test performance. Issue 7 (July 2015) - Kerdijk, Wouter; Cohen‐Schotanus, Janke; Mulder, B Florentine; Muntinghe, Friso L H; Tio, René A
<x xml:space="preserve">Abstract</x> Context Students tend to postpone preparation for a test until the test is imminent, which raises various risks associated with 'cramming' behaviours, including that for suboptimal learning. Cumulative assessment utilises spaced testing to stimulate students to study more frequently and to prevent procrastination. This randomised controlled study investigated how cumulative assessment affects time spent on self‐study and test performance compared with end‐of‐course assessment. Methods A total of 78 undergraduate medical students in a Year 2 pre‐clinical course were randomly assigned to either of two conditions. Students in the cumulative assessment condition were assessed in weeks 4, 8 and 10. Students in the end‐of‐course assessment condition were assessed in week 10 only. Each week, students reported the number of hours they spent on self‐study. Results Students in the cumulative assessment condition (n = 25) spent significantly more time on self‐study than students in the end‐of‐course assessment condition (n = 37) in all weeks of the course except weeks 5, 9 and 10. Overall, the cumulative assessment group spent 69 hours more on self‐study during the course than did the control group, although the control group spent 7 hours more in studying during the final week of the course than did the cumulative assessment group. Students in the cumulative assessment condition scored slightly higher on questions concerning the content of the last part of the course. Conclusions Cumulative assessment encourages students to distribute their learning activities over a course, which leaves them more opportunity to study the content of the last part of the course prior to the final examination. There was no evidence for a short‐term effect of cumulative assessment on overall knowledge gain. We hypothesise that larger positive effects might be found if retention were to be measured in the long term.